MAKNA BENDA SIMBOLIK DALAM KUMPULAN PUISI MAHNA HAURI KARYA HASAN ASPAHANI PENDEKATAN SEMIOTIK MICHAEL RIFFATERRE - Marangga, Samsir (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2020)
The poetry collection "Mahna Hauri" contains narrative poetry and uses two languages, Indonesian and English. This collection of poems has three subtitles, the first part contains "Beberapa Bait Rambut", the second part contains "Beberapa Helai Fabel", the third is about "Kita pun Bertukar Sebelah Sepatu". This division is useful for making it easier for the reader, in selecting subsections of titles contained in poetry books. The formulation of the problems in this research are (1) how are the heuristic, hermeneutic, and hypogram readings in the collection of Hasan Aspani's "Mahna Hauri" poetry? (2) what is the meaning of the symbolic objects contained in Hasan Aspani's collection of poetry "Mahna Hauri"? The objectives of this study were (1) to describe the heuristic, hermeneutic, and hypogram readings of Hasan Aspahani's poetry collection "Mahna Hauri". (2) to describe the meaning of symbolic objects contained in Hasan Aspahani's collection of poetry "Mahna Hauri". This type of research is literature study with a descriptive qualitative approach. The data used in this study were five poems in Hasan Aspani's book of poetry collection "Mahna Hauri". Meanwhile, the data source is Hasan Aspani's poetry collection book "Mahna Hauri". The data collection techniques used include: data reduction, description, drawing conclusions, and validation or verification. The data analysis technique used Michael Riffaterre's semiotic analysis. The results of the analysis of the meaning of the symbolic objects in the five poems contained in Hasan Aspahani's collection of poems "Mahna Hauri" can be concluded as follows: The poem "Bocah Berambut Basah" is a hypogram for the poem ":anak Desa Melihat Surga" by Nugroho Suksmanto. There are at least three meanings of symbolic objects found in the poem "Bocah Berambut Basah". 1) a child, in this poem, a child means innocence, has high curiosity, and is easy to imitate what he sees, 2) mirror, which means a symbol of view, 3) comb, comb means neatness.